Association of serum uric acid with right cardiac chamber remodeling assessed by cardiovascular magnetic resonance feature tracking in patients with connective tissue disease - Tang, Yuanyuan; Yang, Zhaoxia; Wen, Jinyang; Tang, Dazhong; Luo, Yi; Xiang, Chunlin; Huang, Lu; Xia, Liming (Frontiers in Endocrinology, 2024)
Background: Right cardiac chamber remodeling is widespread in patients with connective tissue disease (CTD). Serum uric acid (SUA) is considered a potential independent risk factor for cardiovascular disease and elevated SUA levels are often observed in patients with CTD. The correlation between SUA levels and right cardiac chamber remodeling remains unclear. This study investigated the association of SUA with right cardiac chamber remodeling assessed by cardiac magnetic resonance feature-tracking (CMR-FT) in CTD patients. Methods and results: In this cross-sectional study, a total of 104 CTD patients and 52 age- and sex-matched controls were consecutively recruited. All individuals underwent CMR imaging and their SUA levels were recorded. Patients were divided into three subgroups based on the tertiles of SUA level in the present study. CMR-FT was used to evaluate the right atrial (RA) longitudinal strain and strain rate parameters as well as RV global systolic peak strain and strain rate in longitudinal and circumferential directions for each subject. Univariable and multivariable linear regression analyses were used to explore the association of SUA with RV and RA strain parameters. Compared with controls, CTD patients showed significantly higher SUA levels, but a lower RV global circumferential strain (GCS) and RA phasic strain parameters (all p<0.05), except RA booster strain rate. RV GCS remained impaired even in CTD patients with preserved RV ejection fraction. Among subgroups, patients in the third tertile had significantly impaired RV longitudinal strain (GLS), RV GCS, and RA reservoir and conduit strain compared with those in the first tertile (all p<0.05). The SUA levels were negatively correlated with RV GLS, RV GCS, as well as RA reservoir and conduit strain and strain rates (absolute values of β were 0.250 to 0.293, all P<0.05). In multivariable linear regression analysis, the SUA level still was an independent determinant of RA conduit strain (β=-0.212, P=0.035) and RV GCS (β=0.207, P=0.019). Conclusions: SUA may be a potential risk factor of right cardiac chamber remodeling and is independently associated with impaired RA conduit strain and RV GCS in CTD patients.